Energy, exergy and enviro-economic assessment of productivity enhanced passive double sided vertical convection solar distiller for fresh water production. (December 2020) - Sharon, H.
Highlights: Distiller's performance enhanced at optimum feed water flow rate of 40 kg/d. Distiller's annual average yield is about 12.6 kg/d for absorber area of 3.0 m 2 . Radiation & evaporative heat transfer coefficient are closer at low solar intensity. High exergy efficiency (4.73%) and low distillate production cost (Rs. 2.00/L). Distiller can mitigate 69.36 tons of CO2, 498.70 kg of SO2 and 203.69 kg of NO emission. Abstract: Vertical solar distiller's productivity is similar to other available passive solar stills but it occupies less ground area. Hence, enhancing its productivity is of wide interest for researchers. In general, most of the enhancement techniques increase distiller's capital cost, maintenance cost and distillate production cost which in turn hinder its real time applicability. Hence, enhancing distillate productivity by adopting techniques having minimal impact on distiller's capital cost is an effective option to reduce distillate production cost and increase chance of acceptability among public. In this work, feed water supply rate has been selected as a tool for enhancing distillate productivity of double sided vertical convection solar distiller. Transient mathematical model of distiller is developed and simulated under the climatic condition of Chennai, India to study the impact of geometric parameters and feed water supply rate on its performance, economics and environmental benefits. Enhanced performance of the unit is observed for a vertical absorber area, gap and feed water supply rate of 3.0 m 2, 0.05 m and 40.0 kg/d, respectively. Feed water supply rate below recommended value has positive impact on recovery ratio and negative impact on distillate production rate, energy and exergy efficiency. The unit generated annual average distillate yield of about 12.55 kg/d with recovery ratio, energy and exergy efficiency of 31.70%, 62.16% and 4.73%, respectively. Maximum distillate production cost of the unit is just Rs. 2.00/L (~0.03 USD/L). Maximum energy and finance payback time is within 1 Yr and 8 Yr, respectively. Moreover, its minimum assured emission mitigation potential for 20 Yr life time is about 69.36 tons of CO2, 498.70 kg of SO2 and 203.69 kg of NO. High yield, reasonable distillate production cost and environmental benefits make proposed improved vertical distiller a suitable candidate for potable water production.